'SLOW REVOLUTION' IN SOUTHERN AFRICA: HOUSEHOLD BIOSOCIAL REPRODUCTION AND REGIONAL ENTANGLEMENTS IN THE HISTORY OF CATTLE-KEEPING AMONG NGUNI-SPEAKERS, NINTH TO THIRTEENTH CENTURY CE. (July 2020) - Jimenez, Raevin
Abstract: In the eleventh to thirteenth century, Southern African Nguni-speakers made a counterintuitive choice to begin investing in large herds of cattle. Despite a long-standing knowledge of cattle, the earliest Nguni-speakers did not take to cattle-keeping as a way of life. Rather, the transition came as the result of changing social circumstances as households sought to manage the lifecycles of young men and reliably exploit their labor through gendered and generational expectations of decorum. Nguni-speakers grounded new concepts about cattle in older practices and norms regarding the social reproduction of young men. Agropastoralists situated cattle-keeping among the obligations young men faced after passing through initiation, giving cattle local salience. The transformation unfolded in gendered and generational household choices, but was shaped by the broad context of an increasingly interconnected Southern Africa.